Assessing Public Management Reforms - Gibert, Patrick. author. aut Link
XIII, 218 p.
Keywords: This book examines why many ambitious public management policies do not materialize. Comprehensive reforms do not generate relevant and lasting changes. Yet some evolutions may occur that actually improve the efficiency level inside public administrations. The book identifies how and why such processes may occur. It explores an innovative approach to the way reform policies inside the public are assessed. The opening chapters examine the contributions of different disciplines to the study of change in the public sector, before proposing a framework to better understand management developments. The book then reviews eight crosscutting central government programmes successively launched since the late 1960s, examines how these programmes were designed and constructed, and analyses the ways in which three toolkits are appropriated: dashboards and indicators, cost-benefit analysis, and ex post evaluation. The final chapters examine the links between the development of agencification and the way in which central government proceeds to implement it, and demonstrate why and how the structure of human resources is crucial for initiating change processes. Together, the book proposes lessons for public practitioners as well as for academic purposes. Patrick C. Gibert is Emeritus Professor of Management at the University of Paris-Nanterre, France. An alumnus of the Northwestern Graduate School, his publications examine the ways in which public organizations enact performance management and policy evaluation. He is the co-founder of the journal Politiques et Management Public. Jean-Claude Thoenig is a former research director at the Centre National de la Recherche Scientifique, France. A former associate dean at INSEAD, he led the French Conseil Scientifique de l’Évaluation. His academic contributions cover innovation management, policy implementation and evaluation, intergovernmental relationships, higher education, and research institutions.